Programmed Cell Death and Autophagy in an in vitro Model of Spontaneous Neuroretinal Degeneration - Puertas-Neyra, Kevin; Galindo-Cabello, Nadia; Hernández-Rodríguez, Leticia A.; González-Pérez, Fernando; Rodríguez-Cabello, José Carlos; González-Sarmiento, Rogelio; Pastor, José Carlos; Usategui-Martín, Ricardo; Fernandez-Bueno, Ivan (Frontiers in Neuroanatomy, 2022)
Retinal neurodegenerative diseases are the leading causes of visual impairment and irreversible blindness worldwide. Although the retinal response to injury remains closely similar between different retinal neurodegenerative diseases, available therapeutic alternatives are only palliative, too expensive, or very specific, such as gene therapy. In that sense, the development of broad-spectrum neuroprotective therapies seems to be an excellent option. In this regard, it is essential to identify molecular targets involved in retinal degeneration, such as cell death mechanisms. Apoptosis has been considered as the primary cell death mechanism during retinal degeneration; however, recent studies have demonstrated that the only use of anti-apoptotic drugs is not enough to confer good neuroprotection in terms of cell viability and preservation. For that reason, the interrelationship that exists between apoptosis and other cell death mechanisms needs to be characterized deeply to design future therapeutic options that simultaneously block the main cell death pathways. In that sense, the study aimed to characterize the programmed cell death (in terms of apoptosis and necroptosis) and autophagy response and modulation in retinal neurodegenerative diseases, using an in vitro model of spontaneous retinal neurodegeneration. For that purpose, we measured the mRNA relative expression through qPCR of a selected pool of genes involved in apoptosis (BAX, BCL2, CASP3, CASP8, and CASP9), necroptosis (MLKL, RIPK1, and RIPK3), and autophagy (ATG7, BCLIN1, LC3B, mTOR, and SQSTM1); besides, the immunoexpression of their encoding proteins (Casp3, MLKL, RIPK1, LC3B, and p62) were analyzed using immunohistochemistry. Our results showed an increase of pro-apoptotic and pro-necroptotic related genes and proteins during in vitro retinal neurodegeneration. Besides, we describe for the first time the modulation between programmed cell death mechanisms and autophagy in an in vitro retinal neurodegeneration model. This study reinforces the idea that cell death mechanisms are closely interconnected and provides new information about molecular signaling and autophagy along the retinal degeneration process.